2020
DOI: 10.1002/ange.202011513
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Class of 1H‐MRI Contrast Agents Based on the Relaxation Enhancement Induced on Water Protons by 14N‐Containing Imidazole Moieties

Abstract: This study reports the development of a completely new class of MRI contrast agents, displaying remarkable relaxation effects in the absence of paramagnetic metal ions. Their detection requires the acquisition of images at variable magnetic field strength as provided by fast field cycling imaging scanners. They contain poly‐histidine chains (poly‐His), whose imidazole groups generate 14N‐quadrupolar‐peaks that cause a relaxation enhancement of water protons at a frequency (1.38±0.3 MHz) that is readily detecta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The principles and main features of these two approaches –which we denote decoupling‐recoupling with exchange (D‐REX) and decoupling‐recoupling with saturation transfer (D‐REST) in order to stress their relation to the frequency‐labeled by exchange (FLEX) [31–33] and CEST methods– are introduced in the next section. Thereafter we present results where the efficiency of these methods was used for mapping spectra and images of 17 O, a 0.038 % natural abundance [34,35] isotope of interest in imaging metabolic and functional processes, [15,36,37] as well for spectrally mapping and imaging various 14 N‐containing biomolecules [38‐40] and contrast agents [41,42] . In all cases, this was achieved by observing solely the signal of bulk water.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The principles and main features of these two approaches –which we denote decoupling‐recoupling with exchange (D‐REX) and decoupling‐recoupling with saturation transfer (D‐REST) in order to stress their relation to the frequency‐labeled by exchange (FLEX) [31–33] and CEST methods– are introduced in the next section. Thereafter we present results where the efficiency of these methods was used for mapping spectra and images of 17 O, a 0.038 % natural abundance [34,35] isotope of interest in imaging metabolic and functional processes, [15,36,37] as well for spectrally mapping and imaging various 14 N‐containing biomolecules [38‐40] and contrast agents [41,42] . In all cases, this was achieved by observing solely the signal of bulk water.…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter we present results where the efficiency of these methods was used for mapping spectra and images of 17 O, a 0.038 % natural abundance[ 34 , 35 ] isotope of interest in imaging metabolic and functional processes,[ 15 , 36 , 37 ] as well for spectrally mapping and imaging various 14 N‐containing biomolecules[ 38 , 39 , 40 ] and contrast agents. [ 41 , 42 ] In all cases, this was achieved by observing solely the signal of bulk water.…”
Section: Introductionmentioning
confidence: 99%
“…This was demonstrated thanks to the presence of 14 N atoms of histidine causing a quadrupolar relaxation enhancement (also called Quadrupolar Peak, QP) at 1.39 MHz, well detectable using a Fast Field Cycling NMR relaxometer 28 . The relaxation enhancement is pH dependent in the range 6.5-7.5, thus it acts as a reporter of the nanoparticle or scaffold integrity 28,29 . As it has been demonstrated that in the cancer microenvironment the pH is altered and more acidic than the physiological one 30 , herein, we propose the use of these B and Gd containing pH-sensitive nanoparticles which selectively interact with cell membranes to release the encapsulated drug in the proximity of tumour tissues.…”
mentioning
confidence: 96%
“…In fact, the pKa of histidine in its oligomeric form is approximately 6.8 27 , thus being below pH 7 the imidazole ring is protonated. This occurs also when the oligo-His is conjugated to a PLGA polymeric chain forming a stable nanoparticle 28 . This was demonstrated thanks to the presence of 14 N atoms of histidine causing a quadrupolar relaxation enhancement (also called Quadrupolar Peak, QP) at 1.39 MHz, well detectable using a Fast Field Cycling NMR relaxometer 28 .…”
mentioning
confidence: 99%
See 1 more Smart Citation